2022
DOI: 10.20396/bjos.v21i00.8666469
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dentistry content on instagram® and the use of social networks by brazilian dental students

Abstract: Aim: The aim of our study was to analyze the content related to dentistry published on Instagram® and to investigate the students’ profiles related to the use of social networks in a sample from a Dentistry School. Methods: This study was carried out in two stages. First, research was conducted to analyze content published on Instagram® related to dentistry. The second part investigated the profiles of students’ from a dental school in relation to the use of social networks through a questionnaire. A descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
0
0
Order By: Relevance
“…The findings highlight the prevalence and relevance of Instagram ® in the lives of Dental students, particularly among women and those in the early stages of their professional journey. These findings are in accordance with studies reported by Al-Khalifa et al, 13 Meira et al, 14 and Cumerlato et al 15 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings highlight the prevalence and relevance of Instagram ® in the lives of Dental students, particularly among women and those in the early stages of their professional journey. These findings are in accordance with studies reported by Al-Khalifa et al, 13 Meira et al, 14 and Cumerlato et al 15 …”
Section: Discussionsupporting
confidence: 93%
“…The findings highlight the prevalence and relevance of Instagram ® in the lives of Dental students, particularly among women and those in the early stages of their professional journey. These findings are in accordance with studies reported by Al-Khalifa et al, 13 Meira et al, 14 and Cumerlato et al 15 Mondkar et al, reported that a sizable percentage of people (87%) use the internet either regularly or nearly daily. Additionally, 79% of people use mobile devices to access the internet, making it simple to connect to social networking sites.…”
Section: Discussionsupporting
confidence: 92%
“…For example, using photographs of before and after results can create unrealistic expectations for patients with more difficult cases. (16,17) According to one study, most professional content on social media is intended for health professionals, making engagement between clinicians and patients unlikely. 18 As demonstrated by the Cumerlato et al (16) study, advertising-related posts were the most common, rising from 31,8% in 2.016 to 52,7% in 2.020.…”
Section: Discussionmentioning
confidence: 99%
“…(16,17) According to one study, most professional content on social media is intended for health professionals, making engagement between clinicians and patients unlikely. 18 As demonstrated by the Cumerlato et al (16) study, advertising-related posts were the most common, rising from 31,8% in 2.016 to 52,7% in 2.020. Similarly, promotional publications accounted for 67% of both men and women in our study, indicating an increase in digital marketing and labor competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation